The Effect of Fibrin Clots and Clot-Bound Thrombin on the Development of Platelet Procoagulant Activity - Kumar, Rachana; Béguin, Suzette; Hemker, H Coenraad (Thrombosis and Haemostasis, 1995)
We tested different types of clot for their ability to provoke procoagulant activity in platelets: normal clots from platelet poor plasma (des AABB- or fibrin II clots), similar clots in which the adsorbed thrombin has been inhibited by hirudin, and clots obtained by the action of two snake venom enzymes that release only fibrinopeptide A (des AA- or fibrin I clots). Analogous clots from fibrinogen solutions were also tested.In platelet rich plasma (PRP), where platelet coagulant phospholipids (PCP) are rate limiting for thrombin generation, the addition of any type of clot enhances the generation of thrombin thus it induces the appearance of PCP. Clots containing active adsorbed thrombin are the most potent ones in this respect. Lactate dehydrogenase (LDH) levels do not increase in the course of the thrombin generation so the platelets are not damaged in the process. Non-centrifugable PCP could be demonstrated to appear during the process, so the production of procoagulant phospholipid microparticles must be part of the mechanism. Membrane transbilayer phosphatidyl serine movement (flip-flop) can not be demonstrated in PRP as the activated platelets are caught in the emerging clot.In order to demonstrate flip-flop, we tried to investigate the influence of clots on washed platelets. However, contrary to platelets in a plasma milieu, isolated platelets are damaged by fibrin clots, especially in the presence of thrombin, as can be judged from the appearance of LDHWe conclude that, in PRP, clots induce the appearance of PCP from platelets by vesiculation, possibly accompanied by flip-flop and that thrombin accelerates the process but is not an absolute requirement